Little red dots - Faller, Stéfani (Cadernos de Astronomia, 2025)
Explanatory note about the so-called little red dots (LRDs), observed by the James Webb Telescope. These compact, high-mass objects would have formed at a time when the universe was still quite young, which raises questions within the scientific community, since there wouldn’t be enough time for objects with such pronounced reddish brightness, characteristic of old galaxies, to form.